Determinants of the distance walked in the six-minute walk test at discharge from patients with heart failure (Research, Society and Development, 2023)
Background: The distance walked during the six-minute walk test (6MWD) is predicted measure for mortality and rehospitalization in patients with heart failure. Objective: To identify the determinants of 6MWD at discharge from patients with heart failure. Methods: This is a descriptive and cross-sectional clinical study. Patients aged 18 to 80 years and functional class I to II were eligible. Those who have a type of psychiatric, cognitive or locomotor disorder; atrial fibrillation; use of a fixed frequency heart pacemaker were not eligible. The following were collected from the medical records: name, age, sex, BMI (body mass index); ejection fraction of the left ventricle; hemoglobin; fasting blood glucose; etiology of stay; presence of risk factors for cardiovascular diseases; presence of infection. The muscle strength of the knee extension movement was evaluated by dynamometry, a quality of life with the Nottingham Health Profile (NHP), the previous physical activity level by the International Physical Activity Questionnaire (IPAQ) and the 6MWD. Results: Sixty patients from a final sample (58.3% males, mean age 56.23±10.44 years). Were selected as the variables selected from the multivariate analysis: age (p=0.057), dynamometry (p=0.004), Total NPH (p=0.017) and IPAQ (p=0.018). R=0.72 and R²=0.53 with p